1991
DOI: 10.1111/j.1532-950x.1991.tb00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic Portosystemic Venous Anomaly in the Dog Perioperative Management and Complications

Abstract: Hypotension, hemorrhage, and acute hepatic congestion were common complications during surgical correction of intrahepatic portosystemic venous anomalies in 13 dogs. Acute splanchnic congestion and hyperthermia were the most serious postoperative complications. Three dogs died within 24 hours; 10 dogs are alive and well after 12 to 46 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
96
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(104 citation statements)
references
References 9 publications
7
96
1
Order By: Relevance
“…[2][3][4][5][6][21][22][23] On the other hand, long-term mortality (2.9%) was low in comparison with other studies that reported rates of 7% (3/41), 10% (3/29) and 16% (6/37) respectively. 2,4,5 One possible explanation for this difference was 7 dogs with a guarded prognosis were euthanatized intraoperatively in our study.…”
Section: Discussionmentioning
confidence: 68%
“…[2][3][4][5][6][21][22][23] On the other hand, long-term mortality (2.9%) was low in comparison with other studies that reported rates of 7% (3/41), 10% (3/29) and 16% (6/37) respectively. 2,4,5 One possible explanation for this difference was 7 dogs with a guarded prognosis were euthanatized intraoperatively in our study.…”
Section: Discussionmentioning
confidence: 68%
“…Other investigators have assessed the risk by monitoring venous pressure (3,9,13,14,16,21). False-negative estimates were reported in 2 of 33 dogs (6%) (13), in 2 of 22 dogs (9%) (21), and in 1 of 13 dogs (8%) (14). From these data we conclude that the technically complicated and time-consuming procedure of portal venous pressure monitoring does not produce better results.…”
mentioning
confidence: 68%
“…Using these criteria, a false-negative estimate was made in 11 of 175 cases (6%). Other investigators have assessed the risk by monitoring venous pressure (3,9,13,14,16,21). False-negative estimates were reported in 2 of 33 dogs (6%) (13), in 2 of 22 dogs (9%) (21), and in 1 of 13 dogs (8%) (14).…”
mentioning
confidence: 99%
“…Such approaches can provide surgeons with useful information and knowledge for the safe removal of affected liver parts. Detailed knowledge of the liver vessel anatomy is also crucial to understanding the spatial relationships among liver structures that enable correct interpretation/recognition of (i) radiographic and computed tomography scans, (ii) ultrasound images and (iii) intrahepatic vascular anomalies [9], including extra-or intrahepatic left-and right-sided vessel shunts [4,11,12] and patent venous ducts [17]. Research into hollow liver structure arrangement has been based on the studies of formalin-fixed specimens, angiograms and corrosion casts.…”
Section: Introductionmentioning
confidence: 99%